FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN MANCANEGARA MEMILIH PAKET VOLUNTOURISM DI IVHQ UBUD, BALI - Permatasari Liyanti, Intan; Eka Mahadewi, Ni Putu; Sasrawan Mananda, I Gusti Putu Bagus (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
The development of voluntourism in the world can be recognise from the existence of organizations that provide volunteer travel program. Bali as the icon of Indonesia tourism also become one of destination for voluntourism. Tourist that decide in choosing voluntourism package have its own tourist characteristic. With the presence of tourists who choose the voluntourism package, it is necessary to examine the factors that influence purchasing decisions and their dominant factors. The purpose of this study is to determine tourist characteristic, the factors and dominant factors that influence foreign tourist decision choosing voluntourism package in IVHq Ubud, Bali. Data collection in this research using questionnaire and distributed online by google form to user of volunteer program in IVHq Ubud with total sample of 44 respondents. Sampling technique in this research using  purposive sampling. Data analysis technique using likert scale and factor analysis including validity test, and reliability test then the data processed by the Statistical Package for the Social Science (SPSS) version 18.0 program.  The result of analysis factors show that there are five factors including image factors with eigen value of 6.040, external factor with eigen value of  2.378 , psychology with eigen value of 1.681, physical evidence factor with eigen value  of 1.427, and product factor dengan eigen value 1.025. The dominant factor infuencing foreign tourist decision choosing voluntourism package in IVHq Ubud, Bali is brand/image factor with eigen value  of 6.040.